SEORANG ANAK USIA 13 TAHUN PENDERITA DIABETES MILLITUS TIPE 1 DAN HIPERTIROID DENGAN KENDALI GLIKEMIK BURUK - Amir, Rajibsman (Fakultas Kedokteran, 2025)
Type 1 Diabetes Mellitus due to mediated autoimmune destruction of pancreatic βcell leading to absolute insulin deficiency. This disorder is close related to thyroid autoimmunedisease. Both of them shared autoimmune and genetic predisposition which contribute to cooccurence of Type 1 Diabetes and thyroid disease. T1D is one of the most frequent chronicdiseases in children but can have its onset at any age. In adults, new-onset type 1 diabetesmay be misdiagnosed as type 2 diabetes and is more common than youth-onset T1D. Whenhyperthyroidism occurs in patients with DM, they are at an elevated risk of severehyperglycemia and poor glycemic control